Effectiveness of Behavioural Modification Techniques in Children Having Intellectual Disability Pre and Post Evaluation - Irum Siddique (BJPsych Open)
Aims: To find out the effectiveness of different strategies of behaviour modification techniques on children having intellectual disability in specific time period under controlled setting and compare pre and post scores.